Analisis Manajemen Risiko Pada UMKM Fashion Lokal Korean Style Menggunakan Pendekatan Enterprise Risk Management (ERM): Studi Kasus “MadebyHara” - Intan Nur’aini; Ai Malita Wulandari; Nayla Rubayyina Nugraha; Nuri Triani Anggraeni; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze risk management within the local Korean-style fashion MSME MadebyHara using the Enterprise Risk Management (ERM) approach. A descriptive qualitative method was employed, utilizing direct observation and in-depth interviews with the business owner to identify, assess, and categorize business risks. The findings reveal 14 key risks classified into market, marketing, financial, operational, human resource, and legal–reputation risks. Based on the risk matrix analysis, two risks fall into the high-risk category: intense competition with local Korean-style fashion brands and human error during packing and product delivery. Six risks are categorized as medium-level risks, including rapid changes in fashion trends, decreasing consumer purchasing power, declining social media engagement, unstable material supply, production delays, and customer complaints. Meanwhile, six other risks are identified as low-level risks. The results indicate that marketing and operational aspects represent the most significant sources of risk for MadebyHara. This study recommends several mitigation strategies, such as strengthening branding, enhancing product design innovation, implementing strict Standard Operating Procedures (SOPs) and quality control, diversifying suppliers, and improving workforce competence. Consistent application of ERM is expected to improve business resilience and support the sustainability of MadebyHara in the competitive fashion industry..